2014
DOI: 10.1017/s1041610214002245
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of memory deficits in subjective cognitive decline, mild cognitive impairment, Alzheimer's disease and Parkinson's disease

Abstract: Impaired awareness is an important symptom in aMCI. Yet, given the considerable variability in awareness scores, longitudinal studies are required to evaluate their predictive power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 34 publications
(65 reference statements)
7
75
0
13
Order By: Relevance
“…Lehrner et al 2 have demonstrated that cognitively healthy and MCI patients differ in terms of memory awareness, with the latter group tending to overestimate their performance; moreover, they reported that depression symptoms were associated with more complaints and a lower level of awareness. This finding is similar to ours, with MDD subjects tending to underestimate their memory function, although we did not observe differences between our controls and MCI subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lehrner et al 2 have demonstrated that cognitively healthy and MCI patients differ in terms of memory awareness, with the latter group tending to overestimate their performance; moreover, they reported that depression symptoms were associated with more complaints and a lower level of awareness. This finding is similar to ours, with MDD subjects tending to underestimate their memory function, although we did not observe differences between our controls and MCI subjects.…”
Section: Discussionmentioning
confidence: 99%
“…1 Cognitively healthy elderly persons may over/ underestimate their own cognitive status, providing inaccurate reports. 2 Mild cognitive impairment (MCI) is highly prevalent among elderly persons with depressive symptoms, and cognitive decline may persist even after pharmacological treatment of depression. 3 Despite the high comorbidity between MCI and depression, MCI diagnosis based on DSM-5 criteria requires clinicians to rule out other mental disorders, such as major depressive disorder (MDD), as the cause of cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different concepts were used to define the construct of awareness [12][13][14][15][16][17][18][19][20] , anosognosia [21][22][23][24][25][26][27][28][29][30][31][32] , self-awareness 33,34 , self -appraisal 35 , insight 36,37 , cognitive insight 38 , metacognition [39][40][41] , unawareness of deficits 42 , awareness of deficit 43,44 , awareness of disease 1,45 , awareness of functioning 46 , awareness of cognitive deficits 47 , awareness of disabilities 48 , awareness of performance 49 , unawareness of memory 42,[50][51][52] , anosognosia of memory 53 , awareness of memory deficits 54,55 , awareness of memory function and functional abilities 56 , unawareness of psychosis or behavioral problems …”
Section: Resultsmentioning
confidence: 99%
“…Among them, 13 evaluated only this domain 20,23,27,38,39,41,44,47,[50][51][52][53]55 . Ten studies evaluated awareness of cognitive and functional deficits domains 1,18,20,[33][34][35]40,45,46,54 , nine assessed cognitive and social-emotional functioning domains 12,13,17,24,28,30,36,37,49 , and three focused on cognitive and behavioral impairment domains 14,16,42 . Three researches compared awareness of cognitive, functional and behavioral impairment domains 22,25,32 and four studied the recognition of cognitive, functional, and social-emotional 15,19,29,43 .…”
Section: Resultsmentioning
confidence: 99%